Inkjet Printed Wiring Boards with Vertical Interconnect Access on Flexible, Fully Compostable Cellulose Substrates. Issue 4 (20th December 2017) - Samusjew, Aleksandra; Lassnig, Alice; Cordill, Megan J.; Krawczyk, Krzysztof K.; Griesser, Thomas
Abstract: Cellulose foil is a biodegradable and carbon neutral material that is a poor substrate for most conductive silver inks. Herein, it is reported that a simple solution of silver acetate in 1‐methylimidazole can be used to produce conductive patterns on a commercial packaging foil that is composed almost exclusively from cellulose. The reduction can be carried out thermally or by irradiation with UV light. In the latter case, the printed pattern may become conductive on both sides of the substrate and also exhibits conductivity across the cellulose foil, giving rise to fully printed vertical interconnect access. Control experiments confirm that the cellulose plays a crucial role in completing the reduction of the silver salt, obtaining conductive patterns. Abstract : A novel particle‐free silver inkjet ink is presented that can be used to produce conductive patterns on a biodegradable cellulose foil. The printed patterns can be reduced thermally at mild temperatures or by irradiation with UV light. A method for printing vertical interconnect access is also described.